Internalisasi Birrul Walidain melalui Pondok Ramadan Berbasis ABCD - Muhammad Fauzan Arif; Amir Bandar Abdul Majid; Eli Masnawati; Rifdah Salsabila; Ani Rof’iyah (PT. Karya Inovatif Nusantara, 2026)
The challenge of students' limited recognition of the significance of respecting and following their parents continues to be an issue in character education within educational institutions. This community service initiative was designed to improve students' comprehension of birrul walidain (filial piety) as per Islamic teachings through the Ramadan Boarding School Program at SMA Negeri 20 Surabaya. The initiative utilized lectures, engaging discussions, and question-and-answer sessions presented by university students with guidance from postgraduate instructors. More than 100 students participated in this activity, which lasted for a duration of 90 minutes. Findings indicated that students acquired a deeper insight into the significance of honoring, obeying, and exhibiting positive conduct towards their parents as a crucial component of moral development. The Ramadan Boarding School Program also proved to be a valuable educational platform for fostering moral and character values among the students. Furthermore, the program offered practical opportunities for university students to gain experience in academic communication and carry out community involvement efforts. Consequently, the Ramadan Boarding School Program successfully contributed to the internalization of birrul walidain values and reinforced character education among the students.